Congolese Children at the Congo House in Colwyn Bay (North Wales, Great-Britain), at the End of the 19th Century. Unpublished Documents. - Etambala, Zana Aziza (Afrika Focus, 1987)
In the present study we like to focus the attention on the presence of Congolese children at the Congo House in Colwyn Bay (North Wales, Great-Britain) during the last decade of the 19th century. The idea, which William Hughes conceived and which consisted of educating Congolese, in a first phase, and other African youth, in a second one, never received a just interest. The experiment of Hughes, a former baptist missionary, was a unique specimen for Great-Britain. Henry Morton Stanley and King Leopold II were a little bit involved in the successful start of this initiative. But this article has particularly in view an identification of the Congolese boys and girls who frequented the 'Congo House1 ! KEYWORDS : Colwyn Bay, Congolese children, Education, End of 19th century, W. Hughes